THE INFLUENCE OF ORGANIZATIONAL COMMITMENT AND WORK MOTIVATION TOWARD ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Thasya Nabilla; Roni Faslah; Marsofiyati (Econosains Jurnal Online Ekonomi dan Pendidikan, 2022)
This study aims to determine the effect of organizational commitment and work motivation on organizational citizenship behavior on employees of The Bogor Regency Transportation Service. The research method used is a survey method with a descriptive approach. The population in this study found 357 employees with a research sample of 189 honorary employees. The data analysis technique used is multiple linear regression analysis using the SPSS v.25.0 programs. The results showed that organizational commitment and work motivation had a positive and significant effect on organizational citizenshipbehavior by 60.2% and the remaining 39.8% were influenced by other variables not examined